Invagination of Meckel’s Diverticulum: A Rare Cause of Recurrent Abdominal Pain in a Young Girl (Annals of Medical Research, 2021)
None
Keywords: Meckel’s Diverticulum; Intussusception; Ultrasonography; Computed Tomography.